Prevalence and causes of blindness and vision impairment in Western Uganda: Findings from a rapid assessment of avoidable blindness (RAAB) survey - Mostafa Bondok; Moses Kasadhakawo; John Onyango; Oscar Turya; Khumbo Kalua (PLoS ONE, 2025)
Purpose To determine the prevalence and causes of blindness and vision impairment (VI) among adults aged ≥50 years in Western Uganda. Methods A population-based cross-sectional survey was conducted in Western Uganda (July-August 2023) using RAAB7. Adults aged ≥50 years who had resided in the study districts for at least six months in the past year were eligible. Participants were identified through door-to-door household visits using a two-stage cluster sampling approach. Primary outcomes include prevalence of blindness and VI and its causes. Secondary outcomes include cataract surgical coverage (CSC), effective CSC (eCSC), refractive error coverage (REC), and effective REC (eREC). Results A total of 3,125 participants were examined (54.1% female). The adjusted prevalence of blindness (presenting visual acuity (PVA) <3/60) was 0.9% (95% CI: 0.5–1.3%). Severe, moderate, and mild VI were found in 0.9% (95% CI: 0.4–1.3%), 4.5% (95% CI: 3.3–5.8%), and 3.8% (95% CI: 3.0–4.6%), respectively. Untreated cataract was the leading cause of bilateral blindness (49.4%). The CSC and eCSC at the < 6/12 threshold were 19.7% and 7.3%, respectively. Only 19.4% of 108 operated eyes achieved good outcomes (PVA ≥ 6/12). The main barriers to cataract surgery included lack of awareness (32.8%), cost (23.9%), and perceived lack of need (20.9%). The adjusted prevalence of uncorrected refractive error as a cause of moderate VI was 1.6% (95% CI: 1.1–2.0%), and mild VI was 2.8% (95% CI: 2.2–3.5%). REC was 1.0%, while eREC was 0.6% (95% CI: 0.0–1.4%). Conclusion Blindness and vision impairment remain major public health issues in Western Uganda, primarily due to untreated cataract and uncorrected refractive error. Poor post-operative outcomes highlight the urgent need to improve surgical quality. These findings may guide targeted interventions and policy to strengthen eye care services.